2017
DOI: 10.1038/s41467-017-00505-8
|View full text |Cite
|
Sign up to set email alerts
|

Hit-and-run programming of therapeutic cytoreagents using mRNA nanocarriers

Abstract: Therapies based on immune cells have been applied for diseases ranging from cancer to diabetes. However, the viral and electroporation methods used to create cytoreagents are complex and expensive. Consequently, we develop targeted mRNA nanocarriers that are simply mixed with cells to reprogram them via transient expression. Here, we describe three examples to establish that the approach is simple and generalizable. First, we demonstrate that nanocarriers delivering mRNA encoding a genome-editing agent can eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 58 publications
0
123
0
Order By: Relevance
“…successfully designed a new CAR‐T preparation method which delivered mRNA‐coated nanoparticle into stem cells or T cells from the patients in vitro (Figure 10b). [ 104 ]…”
Section: Targeted and Tumor Environment Responsive Gene Delivery Intomentioning
confidence: 99%
“…successfully designed a new CAR‐T preparation method which delivered mRNA‐coated nanoparticle into stem cells or T cells from the patients in vitro (Figure 10b). [ 104 ]…”
Section: Targeted and Tumor Environment Responsive Gene Delivery Intomentioning
confidence: 99%
“…[ 71 ] Based on this concept, Moffett et al effectively removed the T cell receptor alpha constant region (TRAC) using megaTAL nuclease and abolished the production of non‐cancer‐specific T cell receptors (TCRs), which is an important challenge in improving CAR‐T cell therapy. [ 63 ] To achieve their goal, they delivered mRNA genes to T cells by targeting CD3‐ and CD8‐cells. Their results confirmed that the addition of bioengineered NPs can serve to target specific cell subtypes, stimulate receptor‐mediated endocytosis (namely, the “enhancement of RNA entry by a physiological process without compromising cell viability”), transiently program the expression of genes, and improve the therapeutic potential of both programmed T cells and stem cells.…”
Section: Nanoparticles Potentiate the Generation Of Car Transgene Casmentioning
confidence: 99%
“…Given the essential role of cancer‐associated cells in tumor progression and metastasis, it is not surprising that targeting lymphocytes or hematopoietic stem cells (HSCs) with NPs has proven to be an exciting therapeutic option. [ 63 ] Using this concept, NP‐based gene delivery to tumor‐associated cells can induce the transformation of the immunosuppressive TME into a toxic environment for cancer cells, [ 106 ] which may potentially offer a universal approach to immunotherapy. [ 107 ] Furthermore, NPs appear to be a promising tool to reprogram tumor‐associated cells such as fibroblasts, immune cells (macrophages), dendritic cells (DCs), blood endothelial cells (ECs), and lymphatic vasculators.…”
Section: Nanoparticles As a Potent Platform For Reprogramming Tumor‐amentioning
confidence: 99%
See 1 more Smart Citation
“…[73][74][75][76] Moffett et al and Smith et al each developed a nanocarrier that specifically targets the T cells of patients and delivers mRNA or a DNA plasmid into the T cells to transform them into chimeric antigen receptor (CAR) T cells in situ or ex vivo. [77,78] In this nanocarrier, mRNA or a DNA plasmid encoding the CAR is condensed by incubation with poly(beta-amino ester) (PBAE) 447 polymer and a polyglutamic acid-antibody recognizing cluster of differentiation 3 (CD3), a protein found on the surface of T cells. Through the CD3-specific antibody, the nanocarrier interacts with T cells.…”
Section: Nucleic Acids As Therapeutics Using Nanocarriersmentioning
confidence: 99%